2010
DOI: 10.2319/010709-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Changes Following the Extraction of Premolars in Nongrowing Patients With Bimaxillary Protrusion

Abstract: Objective: To quantify the amount of perioral tissue changes following the extraction of four premolars in patients with bimaxillary protrusion who had nearly completed active growth. Materials and Methods: A literature search was conducted to identify clinical trials that assessed cephalometric perioral soft tissue changes in patients affected by biprotrusion and treated with extractions. Electronic databases (PubMed, ISI WoS Science Citation Index Expanded, and HubMed) were searched. Abstracts that appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 33 publications
(35 reference statements)
2
37
0
11
Order By: Relevance
“…Therefore, improved soft tissue esthetics has become an important treatment objective. Dentoalveolar protrusion, characterized by protrusive and proclined upper and lower incisors and increased procumbency of the lips, 1 is a common chief complaint among Asian patients 2,3 seeking orthodontic care for esthetic reasons. Generally, extraction of first premolars is planned, along with retraction of the anterior teeth with maximum anchorage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, improved soft tissue esthetics has become an important treatment objective. Dentoalveolar protrusion, characterized by protrusive and proclined upper and lower incisors and increased procumbency of the lips, 1 is a common chief complaint among Asian patients 2,3 seeking orthodontic care for esthetic reasons. Generally, extraction of first premolars is planned, along with retraction of the anterior teeth with maximum anchorage.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In the past, soft tissue changes following the extraction of premolars in patients with dentoalveolar protrusion were evaluated primarily with lateral cephalometric radiographs. [5][6][7][8] Leonardi et al 1 reported in their systematic review that the upper and lower lips were retracted 2 to 3.2 mm and 2 to 4.5 mm, respectively, after treatment. However, conventional two-dimensional cephalometry presents several limitations, owing to its midsagittal projection, when investigating the changes of perioral soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Bimaxillary protrusion is a common disease in China and is commonly characterized by protrusive and prominent upper and lower incisors and an increased procumbency of the lips. [1][2][3][4] Typical orthodontic treatment includes extraction of the bimaxillary premolars and anterior tooth retraction, with maximum anchorage achieved through the placement of miniscrews, which enable the practitioners to achieve maximum anterior tooth retraction without undesirable movements of the posterior teeth. Despite the fact that the relationship between maximum anchorage and tooth displacement is well recognized, 5,6 retrospective upper airway analysis after retraction of the large incisors remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Pencabutan gigi premolar pertama digunakan untuk koreksi proklinasi gigi anterior seperti pada maloklusi kelas I dengan protrusi bidental. 4 Maloklusi Angle kelas I bimaksiler protrusi mempunyai hubungan molar normal namun rahang atas maupun bawah protrusi. 3 Kelainan yang paling banyak meyertai maloklusi kelas I adalah gigi berdesakan.…”
Section: Pendahuluanunclassified